An annotated catalogue of the Buprestidae of Iran (Coleoptera: Buprestoidea) - Ghahari, Hassan; Volkovitsh, Mark G.; Bellamy, Charles L. (Zootaxa, 2015)
An annotated taxonomic catalogue of the jewel beetles (Coleoptera: Buprestidae) of Iran is given. Original descriptions and recent revisionary or catalogue data are included along with the distribution, both within and outside of Iran, ecological data and host plant associations, junior synonyms, and comments. A complete bibliography completes the catalogue. In total 428 species and 52 subspecies of jewel beetles belonging to 6 subfamilies (Julodinae, Polycestinae, Galbellinae, Chrysochroinae, Buprestinae, and Agrilinae), 20 tribes, and 38 genera are known from Iran including doubtful records and 4 nomina nuda. It is likely that the number of jewel beetle species from Iran will be between 460–480 and possibly even more species.